Analisis Biaya Produksi Terhadap UMKM Usus Crispy Cap Jempol - Anggoro, Rifky dhimas; Talitha Alwani; Noor Laila Fitriana (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2024)
Production costs are one part of determining the basic price of Products from the Thumbprint Crispy Gut business as well as knowing the price determination and being able to determine how much return on capital has been spent so as to generate a profit. This crispy intestine business is also a business that cannot be separated from the problem of achieving profits and returning capital. The aim of this research is to find out the extent of profits achieved from the thumbprint crispy intestine business. The method used is a descriptive method using a qualitative approach, you can also use research to calculate the cost of production and collect costs that have been incurred for the food business. The results of this research show that the crispy intestine business experiences stable financial conditions and can even achieve maximum results. These costs that have been incurred should be used as an element in calculating the cost of production. It would be best for Crispy Thumbprint intestine business owners to maintain and improve their business as best as possible and innovate if they want their business to survive.